KOMUNIKASI KELUARGA SEBAGAI PENUMBUH KEMANDIRIAN BELAJAR ANAK - S Bekti Istiyanto; Ragil Yusasi (Communicology: Jurnal Ilmu Komunikasi, 2017)
Learning is the need of every human being. By studying then humans can find the ease or solution to the problems it faces. Nowadays learning is not necessarily in formal places like school, but developing with the independent learning process that can take place anywhere. Therefore self-learning requires encouragement to be able to maintain continuity. This is where the role of family communication is considered very important in maintaining the independence of learning children who choose to learn not in formal places or homeschooling. This study used a qualitative approach with informants selected purposively from families that carry out self-learning process for their children. Data collection using observation techniques, in-depth interviews and literature review. The results showed that: family communication is a major basis for the implementation of children's learning process. The more harmonious family communication that is established, the better the independent learning process will be done by their children. Family harmony factors also foster closeness between parents and children; Family communication used in fostering children's learning interest in the early learning process is more applying the process of modeling or imitation; The form of communication applied in an independent learning process that adopts from the Rumah Inspirasi model is a type of primary and circular communication pattern. Primary communication pattern is done in the form of daily conversation in the education process. While the pattern of circular communication by encouraging the child to ask more questions, open out what is in the minds of children so that children have the courage to speak.